Cogan syndrome: a case report and review of the literature - Kahuam-López, Nicolás; Vera-Duarte, Guillermo R.; Pérez-Vázquez , Ana Karen; Navas, Alejandro; Ramirez-Miranda, Arturo; Graue-Hernandez, Enrique O. (Digital Journal of Ophthalmology, 2023)
Cogan syndrome is a rare disease whose etiology is still undetermined. It typically affects men and women between the second and fourth decade of life. We report a case of Cogan syndrome with ocular and audio-vestibular involvement as a systemic manifestation in a 31-year-old woman.